THE STUDY OF RESEARCH MANAGEMENT STANDARDS AT UNIVERSITAS DOKTOR NUGROHO MAGETAN AND INSTITUTO POLITECHNICO DE BETANO TIMUR LESTE - Abdul Gafur; Eko Pujianto; Deslin Monica Sari (CV. Radja Publika, 2023)
This study aims to 1) Analyze the research management standards applied at Universitas Doktor Nugroho Magetan and Instituto Politecnico De Betano, with a focus on the structures, policies, and procedures that support research activities at both institutions. 2) Evaluate the factors that influence the effectiveness of research management at both institutions, including the constraints faced in terms of funding, infrastructure, human resources, and research collaboration both nationally and internationally. 3) Compare research management practices at Universitas Doktor Nugroho Magetan and Instituto Politecnico De Betano, and identify similarities and differences in research management at both higher education institutions from different countries. 4) Provide recommendations based on research findings to improve research management standards at both institutions, in order to support the development of better quality and quantity of research in the future. This study combines qualitative data obtained through in-depth interviews, observations, and quantitative data collected through interviews and questionnaires. The conclusion of this study is that research management at Universitas Doktor Nugroho Magetan (UDN) has implemented eight national standards comprehensively according to SN-Dikti, with a relatively well-established institutional and quality assurance system. Meanwhile, Instituto Politecnico De Betano (IPB) is still in the process of consolidating towards a more structured research management system, in line with the national regulatory framework of Timor-Leste (Decree-Law No. 03/2024 and Ministerial Diploma No. 34/2021). The effectiveness of research management in both institutions is greatly influenced by human resource capacity, infrastructure availability, and policy and funding support. UDNM shows excellence in integrating research into the tridharma and internal quality-based management, while IPB stands out in the flexibility of international partnerships despite being constrained by limited facilities and human resources.